Pattern Analysis of Mosques in Gaza-Palestine by Using GIS (Geographic Information Systems) - Alaeddinne El Jamassi; Farid Al-Qeeq; Zeyad Shehada (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The distribution of mosques is considered one of the problems that residents and planners suffer from in Gaza Strip, thus losing part of their civilized impact and influence. The non observance of planning standards in the distribution of mosques to cope with population growth and urban expansion and the needs of the population on the one hand, and the surplus in number of scattered mosques on the other hand, led to planning problems that affect the role of mosque in community. This research aims to find appropriate planning standards contribute to reduce these problems, and indicate some criteria to choose best locations for future mosques through a case study of neighborhood in Sheikh Radwan district. The importance of this research is analyzing and evaluating the pattern of mosques through descriptive and analytical approach based on using Geographic Information Systems (GIS). This research shows the importance of using the GIS in planning and urban design through selecting the best places to establish new mosques in the future based on the suitable design and planning criteria. These standards are applicable anywhere in Gaza Strip to arrive the available best solutions.